CHINESE TEACHERS’ SOCIAL STATUS AND AUTHORITY IN THE CLASSROOM: A HISTORICAL PERSPECTIVE - Lin, Jing (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1993)
This paper examines the changes in Chinese teachers’ social status and their authority in the classroom, tracing the political ups and downs they experienced since 1949 when the Chinese communist party took over. The paper points out that under the communist government which upholds the dictatorship of the proletariat, Chinese teachers have suffered discriminatory treatment and that great damage has been done to their social status and their authority in the classroom. The paper argues that lack of respect for teachers as human beings and as professionals is inherent in the communist totalitarian system. The paper acknowledges improvement since the economic reform started in 1978, yet maintains that the current political system in China still puts teachers at the mercy of the communist government. Through presenting an extreme case of control, it is hoped that the paper will help educators ail over the world reflect on important issues concerning autonomy and respect for teachers. RÉSUMÉ Cet article analyse les changements intervenus dans le statut social les professeurs chinois et leur autorité en classe, en retraçant les hauts et les bas politiques qu’ils ont traversés depuis 1949 lors de l’avènement des communistes en Chine. L’auteur fait observer que sous le gouvernement communiste qui prône la dictature du prolétariat, les professeurs chinois ont étéfait l’objet de discrimination et que leur statut social et leur autorité en classe ont été sérieusement affectés. L’auteur soutient que le manque de respect pour les professeurs comme êtres humains et comme professionnels est inhérent au régime totalitaire communiste. L’auteur reconnaît qu’il y a eu une amélioration depuis que la réforme économique a débuté en 1978, même si elle affirme que l’actuel régime politique en Chine met les professeurs à la merci du gouvernement communiste. En présentant une étude de cas extrême, on peut espérer que cet article aidera les éducateurs du monde entier à réfléchir aux problèmes importants que pose l’autonomie et le respect des professeurs.